The paradox of biomedical discourse on tobacco: A cognitive ethnobotany study of tobacco uses as traditional medicine in Kledung Village, Temanggung District - Pratama, Muhammad Saputra Agung; Husain, Fadly (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
This article examines local communities' knowledge of tobacco plants, offering a different perspective on the general reality. The paradox of biomedical discourse on tobacco is constructed by the community holistically as traditional medicine. This study uses a longitudinal ethnographic qualitative approach. Data were obtained through participant observation and in-depth interviews with tobacco farmers, tobacco smokers, community leaders, and cultural experts. The researchers also collected ethnobotanical inventory data using the triad test and pile sorting techniques to identify plants used for medicinal purposes. The results of this study show that tobacco is associated with rituals and medicine, thereby constructing a perspective on the paradox of biomedical discourse. Tobacco is legally consumed in the form of rokok lintingan to relieve stress, warm the body, and treat hoarseness. In addition, the community uses it to care for teeth and treat external wounds with its sap. This study reveals the existence of holistic cognitive ethnobotany practices in traditional medicine. Domain analysis found that ecological conditions determine the emergence of interactions between the community and tobacco plants, which serve as a